The Influence of Twin Date Promos on Impulsive Buying Hijab Purchases at Shopee in an Islamic Perspective - Afrohk, Siti Nur; Meilina, Firnanda; Effasa, Ahmad Saifurriza; Rochmayanti, Dewi (Proceeding International Conference on Islamic Economics and Business (ICIEB), 2024)
Indonesian people have a tendency to spontaneously buy products outside their shopping list or what is called impulse buying. It turns out, there are factors behind why people often shop unplanned. First, there is a desire to buy, but can only buy it now (40%), a form of self-appreciation or self-reward (39%), tempted by attractive promotions from sellers (35%). The products most frequently purchased also vary, such as product categories including fashion. We use a quantitative descriptive approach, where we distribute questionnaires and interviews. Using the cluster random sampling method in Kanor District, Bojonegoro Regency with a total sample of 35 respondents. From the results of the tests carried out, it is known that the data is statistically correct, so the correlation number obtained in the validity test (r-calculation with a range between 0.339-0.690 must be compared and not greater than the critical number of the correlation table (r-table) of 0.2869 with a level of significance is 5% in degrees of freedom (df=n- 2). Meanwhile, based on the reliability test results obtained, Cronbach’s alpha is 0.787 for variable valid, then the results of the simple linear regression test can be seen from the table of significance value (Sig) of 0.02 where this value is less than the probability of 0.05 which means that there is an influence of the twin date promo (X) on impulsive buying (Y).